Effect of variations in treatment regimen and liver cirrhosis on exposure to benzodiazepines during treatment of alcohol withdrawal syndrome - Pavel Gershokovich; Kishor M Wasan; Charles Ribeyre; Fady Ibrahim; John H McNeill (BioExcel Publishing Ltd, 2015)
Purpose: Benzodiazepines (BDZs) are the drugs of choice to prevent the symptoms of alcohol withdrawal syndrome (AWS). Various treatment protocols are published and have been shown to be effective in both office-managed and facility-managed treatment of AWS. The aim of this scientific commentary is to demonstrate the differences in the expected exposure to BDZs during AWS treatment using different treatment regimens available in the literature, in patients with or without alcoholic liver cirrhosis. Methods: Diazepam and lorazepam AWS protocols were examined and reviewed in the literature, and blood plasma levels were examined and compared, respectively. Results: Considerable variation in the blood levels with the different dosing schedules was found. Because the drugs are metabolized differently, we have also shown that liver disease affects the blood levels of diazepam, but not of lorazepam. Conclusions: Differences in treatment regimens, the choice of BDZ, as well as the presence of liver cirrhosis can substantially alter the exposure of patients to drugs used for AWS treatment. Outpatient treatment of AWS has been shown to be relatively safe and effective for the treatment of AWS but patients should be carefully monitored.